An analysis of educator development in praxis : with specific reference to the Department of Economic and Management Sciences of secondary schools in Mamelodi - Malan, Lianne Priscilla (University of Pretoria, 2013)
Dissertation (M.Admin)--University of Pretoria, 2006.